Buddhist Mahâyâna texts - Cowell, Edward B.; Müller, Friedrich Max; Takakusu, Junjirō; Aśvaghoṣa ca. 1./2. Jh. (The Sacred books of the East, 1894)
pt. 1. The Buddha-karita of Asvaghosha, translated from the Sanskrit by E. B. Cowell.--pt. 2. The larger Sukhâvatî-vyûha, the smaller Sukhâvatî-vyûha, the Vagrakkedikâ, the larger Pragñâ-pâramitâ-hridaya-sûtra, the smaller Pragñâ-pâramitâ-hridaya-sûtra, translated by F. Max Müller. The Amitâyur dhyâna-sûtra, translated by J. Takakusu.